2015
DOI: 10.4049/jimmunol.1401132
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Inflammatory Pathways in Testicular Macrophages Provides a Rationale for Their Subdued Inflammatory Capacity

Abstract: Spermatogenic cells express cell-specific molecules with the potential to be seen as “foreign” by the immune system. Owing to the time difference between their appearance in puberty and the editing of the lymphocyte repertoire around birth, local adaptations of the immune system coined immune privilege are required to confer protection from autoattack. Testicular macrophages (TM) play an important role in maintaining testicular immune privilege and display reduced proinflammatory capacity compared with other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
66
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 45 publications
3
66
0
3
Order By: Relevance
“…Similarly, the majority of resident macrophages of the testis are also categorized *Institute of Anatomy and Cell Biology, Justus-Liebig-University of Giessen, Giessen 35392, Germany; as M2 macrophages. In support, several in vitro studies showed that the treatment of TM with inflammatory stimuli induced the secretion of large amounts of IL-10 and a low amount of TNF-a (4,13). Moreover, TM activate the anti-inflammatory STAT3 signaling pathway (4).…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Similarly, the majority of resident macrophages of the testis are also categorized *Institute of Anatomy and Cell Biology, Justus-Liebig-University of Giessen, Giessen 35392, Germany; as M2 macrophages. In support, several in vitro studies showed that the treatment of TM with inflammatory stimuli induced the secretion of large amounts of IL-10 and a low amount of TNF-a (4,13). Moreover, TM activate the anti-inflammatory STAT3 signaling pathway (4).…”
mentioning
confidence: 89%
“…In support, several in vitro studies showed that the treatment of TM with inflammatory stimuli induced the secretion of large amounts of IL-10 and a low amount of TNF-a (4,13). Moreover, TM activate the anti-inflammatory STAT3 signaling pathway (4).…”
mentioning
confidence: 89%
See 3 more Smart Citations